Efusi Perikard Hemoragik pada Penderita Leukimia Mielo-Monoblastik Akut - I Made Windutama; Ali Aspar Mappahya; Tutik Harjianti; Fachruddin Benyamin (Jurnal Kardiologi Indonesia, 2007)
A case of a 23 year-old man with haemorrhagic pericardial effusion has been reported. The man came to the hospital due to chest pain, shortness of breath and fever for 5 days. A pericardial effusion was suggested by observing ECG and chest X-ray, later it was proved by echocardiography. Pericardiocentesis was performed, and 650 cc of haemorrhagic fluid was taken out; his condition im-proved dramatically. Acute leukemia has been suggested as the cause, due to high level of White Blood Count. Diagnosis of Acute Myelomonoblastic Leuke-mia (AML) was confirmed by peripheral blood stain and bone marrow aspiration examination. From patient’s history, physical examination, and other tests, no other diseases could suspected as the cause of this hemorrhagic pericardial effu-sion. Chemotherapy of daunorubicin and cytosine-arabinoside was planned for the treatment, but the patient rejected. He was discharged in relatively good condition although the prognosis is still bad.